2012
DOI: 10.1134/s1022795411110093
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the meiotic recombination frequency in transgenic tomato hybrids expressing recA and NLS-recA-licBM3 genes

Abstract: To study and induce meiotic recombination in plants, we generated and analyzed transgenic tomato hybrids F 1 RecA and F 1 NLS recA LicBM3 expressing, respectively, the recA gene of Escherichia coli and the NLS recA licBM3 gene. It was found that the recA and NLS recA licBM3 genes are inherited through the maternal and paternal lineages, they have no selective influence on the pollen and are contained in tomato F 1 RecA and F 1 NLS RecA LicBM3 hybrids outside the second chromosome in the hemizygous state. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This suggested that the expression of the recA gene in plant cells in prophase I of meiosis can also change the number and distribution of crossover exchanges between homologous chromosomes (Komakhin et al, 2010). It was later shown that the expression of the recA gene from E. coli under the control of a strong and constitutive CaMV35S promoter in cultivated tomato leads to an increase in the frequency of meiotic recombination between the wv and d genes of chromosome 2 by 50 % compared with the non-transgenic control (Komakhin et al, 2012).…”
Section: Stimulation Of Meiotic Crossing Over At the Stage Of Homolog...mentioning
confidence: 99%
“…This suggested that the expression of the recA gene in plant cells in prophase I of meiosis can also change the number and distribution of crossover exchanges between homologous chromosomes (Komakhin et al, 2010). It was later shown that the expression of the recA gene from E. coli under the control of a strong and constitutive CaMV35S promoter in cultivated tomato leads to an increase in the frequency of meiotic recombination between the wv and d genes of chromosome 2 by 50 % compared with the non-transgenic control (Komakhin et al, 2012).…”
Section: Stimulation Of Meiotic Crossing Over At the Stage Of Homolog...mentioning
confidence: 99%